CONCEPTUALIZING WORK ENGAGEMENT AND KNOWLEDGE SHARING TO INCREASE ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Yuliantini, Tine; Ramli, Yanto; Kuswibowo, Christian; Zulfikar, Renno Reymond Okto; Soelton, Mochamad (Faculty of Economic and Business, University of Pasundan, 2024)
This research aims to analyze and test the influence of Work Engagement and Knowledge Sharing on Organizational Citizenship Behavior which is mediated by job satisfaction. Quantitative research using questionnaire collection techniques and SEM Smart-PLS, with a saturated sample of 190 employees. Finding, Work Engagement has a positive and significant effect on Organizational Citizenship Behavior. Knowledge Sharing does not affect Organizational Citizenship Behavior. Work Engagement and Knowledge Sharing has a positive and significant effect on Job Satisfaction. Job Satisfaction has a positive and significant effect on Organizational Citizenship Behavior. Job Satisfaction can mediate the influence of Work Engagement on Organizational Citizenship Behavior. Job Satisfaction is unable to mediate the influence of Knowledge Sharing on Organizational Citizenship Behavior. Anomalous findings, employees' high application of work procedures, and having experience appropriate to their current job, encourage employees to respect each other among co-workers even though they are not doing work outside their scope.